The Therapeutic use of Probiotics in Patients with Ulceractive Retocolitis: A Systematic Review (Global Journal of Medical Research, 2022)
Ulcerative Colitis (UC) is considered a multifactorial disease, its prevalence and incidence may vary according to genetics, environment and intestinal microbiota, these factors alter the balance of the immune response of the intestinal mucosa and thus increase the inflammation reaction. The use of probiotics has been studied as a therapeutic form that can help in the balance of the intestinal microbiota along with drug therapy, which can contribute to the remission of the disease. The present study is a narrative literature review that aims to evaluate the effectiveness of probiotics in treatment of UC as part of the diet. The most relevant studies published on the subject between 2004 and 2021 were analyzed using the MEDLINE (Medical Literature Analysis and Retrieval System Online), SciELO (Scientific Electronic Library Online) and Cochrane Library databases. For the search strategy, the following combinations of keywords were used: ulcerative colitis, probiotics, inflammatory bowel diseases, gastrointestinal microbiome.
Keywords: ulcerative colitis probiotics inflammatory bowel diseases gastrointestinal microbiome